Children's identification of familiar songs from pitch and timing cues - Volkova, Anna; Trehub, Sandra E.; Schellenberg, E. Glenn; Papsin, Blake C.; Gordon, Karen A. (Frontiers in Psychology, 2014)
The goal of the present study was to ascertain whether children with normal hearing and prelingually deaf children with cochlear implants could use pitch or timing cues alone or in combination to identify familiar songs. Children 4-7 years of age were required to identify the theme songs of familiar TV shows in a simple task with excerpts that preserved (1) the relative pitch and timing cues of the melody but not the original instrumentation, (2) the timing cues only (rhythm, meter, and tempo), and (3) the relative pitch cues only (pitch contour and intervals). Children with normal hearing performed at high levels and comparably across the three conditions. The performance of child implant users was well above chance levels when both pitch and timing cues were available, marginally above chance with timing cues only, and at chance with pitch cues only. This is the first demonstration that children can identify familiar songs from monotonic versions—timing cues but no pitch cues—and from isochronous versions—pitch cues but no timing cues. The study also indicates that, in the context of a very simple task, young implant users readily identify songs from melodic versions that preserve pitch and timing cues.